2022
DOI: 10.1111/epi.17332
|View full text |Cite
|
Sign up to set email alerts
|

Precision medicine for genetic epilepsy on the horizon: Recent advances, present challenges, and suggestions for continued progress

Abstract: The genetic basis of many epilepsies is increasingly understood, giving rise to the possibility of precision treatments tailored to specific genetic etiologies. Despite this, current medical therapy for most epilepsies remains imprecise, aimed primarily at empirical seizure reduction rather than targeting specific disease processes. Intellectual and technological leaps in diagnosis over the past 10 yearshave not yet translated to routine changes in clinical practice. However, the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 100 publications
1
49
0
Order By: Relevance
“…Epilepsy is caused by excessive abnormal discharge of nerve cells in the brain. Persistent seizures can lead to oxidative stress and inflammation in the brain, damage brain tissue, and cause cognitive dysfunction ( Knowles et al, 2022 ). Puerarin is able to improve epilepsy-induced brain damage through anti-inflammatory, antioxidant, and anti-apoptotic effects, but the exact mechanism is unclear ( Xie et al, 2014 ).…”
Section: Puerarin Regulates Pi3k/akt Signal Pathway To Protect the Ne...mentioning
confidence: 99%
“…Epilepsy is caused by excessive abnormal discharge of nerve cells in the brain. Persistent seizures can lead to oxidative stress and inflammation in the brain, damage brain tissue, and cause cognitive dysfunction ( Knowles et al, 2022 ). Puerarin is able to improve epilepsy-induced brain damage through anti-inflammatory, antioxidant, and anti-apoptotic effects, but the exact mechanism is unclear ( Xie et al, 2014 ).…”
Section: Puerarin Regulates Pi3k/akt Signal Pathway To Protect the Ne...mentioning
confidence: 99%
“…Probably, genomic studies of epileptic disorders have demonstrated one of the most successful explorations of monogenic causes in a heterogeneous group of diseases. These data have been extensively used for understanding molecular mechanisms and developing treatments for this devastative condition [ 1 , 2 ]. However, in contrast to monogenic epilepsies, epileptic disorders caused by chromosomal aberrations are rarely addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Evidently, individual phenotypic features contain valuable information to guide variant interpretation. Knowledge of variant functional effects and genotype-phenotype correlations facilitates a timely diagnosis, informs genetic counselling, and offers therapeutic and prognostic guidance to the clinician (25). However, variant interpretation requires causal evidence generated by electrophysiological experiments which are relatively time-consuming and expensive.…”
mentioning
confidence: 99%